Performance Evaluation of CDMA Mobile Cellular System Using Smart Antenna - Abdulsattar M. Ahmad; Kaydar M.Quboa; Reem B. Saadallah (PROSPECTIVE RESEARCHES, 2023)
In the last few years, the demand for mobile communication services has been increased tremendously. However, there is no proportionate increase in the allocated spectrum. As a result, there is an urgent need for new techniques to improve system spectral efficiency. The use of smart antenna at the base station divides the space into spatial dimension using Space Division Multiple Access (SDMA) technique, which results in maximizing the capacity of cellular system and improving system performance. In this paper, the Bit Error Rate (BER) performance of asynchronous reverse link Code Division Multiple Access (CDMA) mobile cellular system is simulated, taking into account Rayleigh fading channel, convolutional encoder, Viterbi decoder, and Rake Receiver. Also, smart antenna is simulated using Linearly Constrained Minimum Variance (LCMV) beamforming algorithm. The results show that using smart antenna at the base station of mobile system has a significant improvement on CDMA system performance and capacity.